Features of Level Crossing Construction with the Use of Dual Gauge (1520/1435 мm) on the Ukrainian Railway Network - Kurhan, M. B.; Ivanov, R. V. (Science and Transport Progress, 2025)
Purpose. The purpose of the study is to justify and develop technical solutions for the construction of railway level crossings on dual gauge tracks (1520/1435 mm), taking into account modern technologies and operational requirements within the Ukrainian railway network. The lack of unified and optimized solutions hinders the pace of dual gauge implementation on key network segments. To address this issue, an analysis was conducted of existing international and domestic regulatory documents related to the construction of level crossings on dual gauge tracks. Various technological solutions and materials for level crossing decks (rubber-cord, reinforced concrete, and combined types) were examined and compared, with an assessment of their operational and economic characteristics. Methodology. To select the most rational design option for level crossing decks, the study employed methods of systems analysis as well as the Analytic Hierarchy Process (AHP) to substantiate technical decisions. The methodology involves examining the specific features of constructing crossings on dual gauge track, selecting optimal materials and technologies capable of ensuring safety, reliability, and cost-effectiveness for the successful integration of the Ukrainian railway into the European rail system. Findings. A hierarchy of criteria was developed, followed by pairwise comparisons, calculation of weight coefficients, and a comprehensive evaluation of alternatives. The application of AHP made it possible to determine the priority of different crossing deck types based on criteria such as durability, cost, vibration resistance, noise absorption, and maintenance complexity. Recommendations were provided for the implementation of modern level crossing construction technologies on the Ukrainian railway network. Originality. For the first time in the context of Ukraine, a systematic analysis and efficiency assessment of modern level crossing deck types for dual gauge was conducted. This includes the application of the AHP method for multi-criteria decision-making. Practical value. The results of this research can be used by the technical and design departments of Ukrzaliznytsia in developing and implementing projects on sections with dual gauge tracks, by track component manufacturers to adapt their products to modern requirements, and by design organizations in substantiating the selection of technological solutions.